Factors Contributing to Students' Willingness to Communicate during English Day Program: A Case Study at SMK Putra Indonesia Malang - Zumrotul Auliyah; Wahyu Diny Sujannah (STAIN Sultan Abdurrahman Kepulauan Riau, 2023)
A lot of habituations are needed to get students accustomed to communicating using a foreign language. One of the habits that schools can hold is through outside classroom program, such as English Day program by SMK Putra Indonesia Malang, held weekly to create an English environment for students to develop their speaking skills. However, in practice, students’ willingness to communicate (WTC) was considered low based on the initial observations conducted by one of the researchers. The present study aimed to investigate the factors contributing to WTC during the English Day program. Using a case study through interview and observations, the participants were eight tenth grade students of Industrial Chemical and Industrial Pharmacy classes represented by high and low achievers. The results showed that there were five factors influence their WTC during the English Day Program, including their surroundings, being afraid of committing grammatical mistakes, lack of vocabulary knowledge, lack of pronunciation mastery, and shyness. Thus, English teachers are recommended to encourage students to speak more through fun learning activities in the classroom. Moreover, further researchers are suggested to conduct research on a wider sample to know the main factor contributing to low WTC during the English Day program.